Reconstruccion del paisaje del caldenal pampeano en los ultimos 250 años - Duáart, E.G.=700 1 Chirino, C.C.; Morici, E.A.; Peinetti, R.H.
(Es, En)
Ilus., 24 ref.
Keywords: BOSQUES; PROSOPIS; DEFORESTACION; DEGRADACION; ECOLOGIA FORESTAL; HISTORIA; PAISAJE; INCREMENTO DE DIAMETRO; ARGENTINA; PROSOPIS CALDEEN